Glutenase and collagenase activities of wheat cysteine protease Triticain-α: Feasibility for enzymatic therapy assays. (May 2015) - Savvateeva, Lyudmila V.; Gorokhovets, Neonila V.; Makarov, Vladimir A.; Serebryakova, Marina V.; Solovyev, Andrey G.; Morozov, Sergey Yu.; Reddy, V. Prakash; Zernii, Evgeni Yu.; Zamyatnin, Andrey A.; Aliev, Gjumrakch
Graphical abstract: Abstract: Insufficient and/or improper protein degradation is associated with the development of various human pathologies. Enzymatic therapy with proteolytic enzymes aimed to improve insufficient proteolytic activity was suggested as a treatment of protease deficiency-induced disorders. Since in many cases human degradome is incapable of degrading the entire target protein(s), other organisms can be used as a source of proteases exhibiting activities distinct from human enzymes, and plants are perspective candidates for this source. In this study recombinant wheat cysteine protease Triticain-α was shown to refold in vitro into an autocatalytically activated proteolytic enzyme possessing glutenase and collagenase activities at acidic (or close to neutral) pH levels at the temperature of human body. Mass-spectrometry analysis of the products of Triticain-α-catalyzed gluten hydrolysis revealed multiple cleavage sites within the sequences of gliadin toxic peptides, in particular, in the major toxic 33-mer α-gliadin-derived peptide initiating inflammatory responses to gluten in celiac disease (CD) patients. Triticain-α was found to be relatively stable in the conditions simulating stomach environment. We conclude that Triticain-α can be exploited as a basic compound for development of (i) pharmaceuticals for oral administration aimed at release of the active enzyme into the gastric lumen for CD treatment, and (ii) topically active pharmaceuticals for wound debridement applications.